2005
DOI: 10.1177/08830738050200071301
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole in Children and Adolescents: Clinical Experience

Abstract: Despite few supportive data, aripiprazole was being administered to children and adolescents for management of mood instability, aggression, and psychosis. Using a retrospective review (n = 11) and prospective recruitment (n = 6), 17 children and adolescents received aripiprazole 5 to 20 mg/day. Only 4 of 16 bipolar and autistic subjects (25%) demonstrated reduced aggression without adverse events, and the symptoms of 2 of 4 psychotic subjects improved. Coadministration of sedative medications (particularly gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Additionally, although Sam did not gain significant weight, he was also extremely physically active. Other studies of aripiprazole in youth have found modest increases in weight [Murphy et al, 2005;Rugino and Janvier, 2005] so conclusions that can be made about safety and tolerability are limited. Further controlled research is needed to clarify the efficacy of atypical antipsychotic augmentation in treatment resistant OCD patients, and if this approach has superior efficacy and tolerability to cognitive-behavioral and other pharmacologic approaches.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, although Sam did not gain significant weight, he was also extremely physically active. Other studies of aripiprazole in youth have found modest increases in weight [Murphy et al, 2005;Rugino and Janvier, 2005] so conclusions that can be made about safety and tolerability are limited. Further controlled research is needed to clarify the efficacy of atypical antipsychotic augmentation in treatment resistant OCD patients, and if this approach has superior efficacy and tolerability to cognitive-behavioral and other pharmacologic approaches.…”
Section: Discussionmentioning
confidence: 96%
“…Aripiprazole is an atypical antipsychotic medication that works via partial dopaminergic and serotonin 1A receptor agonist activity, and has fewer side effects when compared to other atypicals [Rugino and Janvier, 2005]. To date, there is no research on using aripiprazole to augment treatment for pediatric OCD patients who continue to experience residual symptoms following treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, neuroscience might provide a computational underpinning for the idea that the atypical antipsychotics are beneficial for adolescents with conduct disorder and psychopathic traits. However, it should be noted that atypical antipsychotics have considerable side effects 176 , including weight gain 177 and type 2 diabetes mellitus 178 . As such, future studies should addresses whether these compounds do indeed normalize the patient’s pathophysiology.…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…Aripiprazole is an atypical antipsychotic medication that works via partial dopaminergic, 5-HT1A, 5-HT2A and 5-HT2B receptor agonist activity (Rugino and Janvier 2005).…”
Section: Introductionmentioning
confidence: 99%